2016
DOI: 10.1002/jmv.24473
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinases in the pathogenesis of childhood gastroenteritis

Abstract: Matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) have been implicated in the pathogenesis of gastrointestinal diseases, such as rotavirus gastroenteritis (GE). Kinetics of these biomarkers were examined in paired serum samples collected from bacterial enteritis patients with Campylobacter (n = 2) and Salmonella (n = 4) and viral GE patients with rotavirus (n = 27), norovirus (n = 25), and adenovirus (n = 11). At the time of hospital admission, all viral GE patients demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…11 According to research findings, rotavirus that causes intestinal infection can also be located to extraintestinal tissues (e.g., heart, liver and central nervous system) by virtue of RNA reverse transcriptase (RT) to cause viral infections of associated tissues; in severe cases, tissue damage may also be incurred. [12][13][14][15] The function of the intestinal mucosal barrier in infants is poor. The virus can enter the lymph circulation and blood circulation of the body through the intestinal mucosal barrier, which causes infection of extraintestinal organs and immaturity of intestinal immune function in infants.…”
Section: Discussionmentioning
confidence: 99%
“…11 According to research findings, rotavirus that causes intestinal infection can also be located to extraintestinal tissues (e.g., heart, liver and central nervous system) by virtue of RNA reverse transcriptase (RT) to cause viral infections of associated tissues; in severe cases, tissue damage may also be incurred. [12][13][14][15] The function of the intestinal mucosal barrier in infants is poor. The virus can enter the lymph circulation and blood circulation of the body through the intestinal mucosal barrier, which causes infection of extraintestinal organs and immaturity of intestinal immune function in infants.…”
Section: Discussionmentioning
confidence: 99%
“…As Campylobacter infections are concerned, the data are scarce but some experimental studies have suggested MMPs, such as MMP-9, to have a role in campylobacteriosis in mice [22,23]. In a study on childhood gastroenteritis, two Campylobacter and four Salmonella patients were included and showed elevated serum concentrations of MMP-9 and TIMP-1 as compared to healthy controls [24]. Here, we could show enhanced systemic response of MMP-8 and MMP-9 as well as of their regulators MPO, HNE and TIMP-1 in both Campylobacter and Salmonella patients.…”
Section: Discussionmentioning
confidence: 99%